Trends in incidence of uterine cancer in England, 1985-2017. (20th October 2021) - Apata, A; Bannister, P; Memon, A
Abstract: Background: Cancer of the corpus uteri (hereafter, uterine cancer) is the fourth most common cancer in women in the UK, accounting for 5% of all cancers in women. We conducted a retrospective population-based cohort study to examine whether there have been changes in the incidence of uterine cancer in England during the past four decades. Methods: Individual level data for women diagnosed with uterine cancer in England during 1985-2017 were obtained from the Office for National Statistics/Public Health England. Average annual incidence rates were calculated by two age categories (0-49, 50+ years) and all ages combined during the six five-year time periods (1985-89 to 2010-14) and the recent three-year period (2015-17). The percentage change in incidence was calculated as change in the average annual incidence rate from the first (1985-89) to the last time period (2015-17). Index of Multiple Deprivation (IMD) quintiles (2015-17) were examined to determine the social gradient of the disease. Results: During the 33-year study period, a total of 169, 768 women with uterine cancer were registered in England. In women aged 0-49 years, the average annual incidence rates increased by about 51% (from 1.8/100, 000 in 1985-89 to 2.8/100, 000 in 2015-17), and in women aged 50+ years, the rates increased by about 74% (from 39.0/100, 000 in 1985-89 to 67.7/100, 000 in 2015-17.). At all ages combined, the rates increased by 88%. With regard to the social gradient, in the young age group the highest proportion (46%) of cases occurred in women from the most deprived areas, whereas in the older age-group the highest proportion (43%) occurred in women from the least deprived areas. Conclusions: There has been a steady and substantial increase in the incidence of uterine cancer in England over the last four decades. The observed dichotomy in risk between the young and older women by social gradient needs further investigation. Key messages: Considering that 34% of the cases of uterine cancer in the UK are associated with obesity, the study informs formulation of public health programmes to reduce the prevalence of obesity. The difference in risk between the young and older women by social gradient highlights the importance of reducing health and social inequalities.